2022
DOI: 10.30880/jtet.2022.14.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Project-Based Learning On 4Cs Skills of Vocational Students in Higher Education

Abstract: The results of the previous study showed that theimplementation of the project which is based on the potential of the students’ region was better in improving soft skills, engagement and core competencies of learning for students. This study aims to continue the investigation on revealing the effectiveness of the model in improving the students’ 4Cs skills. It is driven by educational needs in this 21st century which requires vocational students to have those skills to adapt to the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…The results of this study also are in line with Moulidah[46] finding, it provides information of problem-based, CBI, and flipped learning effectiveness in improving 4C skill. Event though, this research finding contradict with Karabulut finding[39].Vocational education is an institution that can focus on developing competence and expertise in the vocational field[47]-[51]. Based on the finding, it showed that through implementation of PBL-cflip, it gave freedom for students to develop thinking skills in learning and seek information to solve case in clinical refraction.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The results of this study also are in line with Moulidah[46] finding, it provides information of problem-based, CBI, and flipped learning effectiveness in improving 4C skill. Event though, this research finding contradict with Karabulut finding[39].Vocational education is an institution that can focus on developing competence and expertise in the vocational field[47]-[51]. Based on the finding, it showed that through implementation of PBL-cflip, it gave freedom for students to develop thinking skills in learning and seek information to solve case in clinical refraction.…”
mentioning
confidence: 61%
“…Vocational education is an institution that can focus on developing competence and expertise in the vocational field [47]- [51]. Based on the finding, it showed that through implementation of PBL-cflip, it gave freedom for students to develop thinking skills in learning and seek information to solve case in clinical refraction.…”
Section: Fig 3 Qq Plots Of Normality Testmentioning
confidence: 99%
“…Battelle for Kids (2019) proposes a model visually represented as a rainbow with different components: Life and Career Skills, Learning & Innovation skills-4Cs, Information, Media & Technology Skills, Key Subjects -3Rs & 21 st Century Themes. The 4C from Battelle for Kids stands for (1) creativity and innovation, (2) critical thinking and problem solving, (3) communication, and (4) collaboration (Syahril et al, 2022;Thornhill-Miller et al 2023) and are quite like the "Competencies" from the report by World Economic Forum (2015).…”
Section: St Century Skillsmentioning
confidence: 99%
“…The development of Industry 4.0, the digitalization of everyday life, the post-pandemic effect on social issues, and the technological development of processes and practices in different fields are causing an increasing interest in Education 4.0 and skills for the 21st century Syahril et al, 2022). "Technology is leading to massive changes in the economy, in the way we communicate and relate to each other, and increasingly in the way we learn.…”
Section: Education Model For Future 1 Introductionmentioning
confidence: 99%
“…The policy aims to provide students with skills ready to be implemented in the workplace, especially aspects of information technology that focus on the quality of human resources ready to compete. It is a form of implementation of higher education in building 21st-century skills in students with web-based learning models, blended, e-learning, mobile, and distance learning [13][14][15]. Implementing the Independent Campus the curriculum requires all universities to implement information technology-based learning media innovations using digital media, such as learning videos, interactive multimedia, augmented reality, virtual reality, mixed reality, and hologram media [16][17][18].…”
Section: Introductionmentioning
confidence: 99%